Infectivity Study of Streptococcus Phocae to Seven Fish and Mammalian Cell Lines by Confocal Microscopy - Cortez-San Martin, M (2012)
Streptococcus phocae is a beta-haemolytic bacterium that causes systemic infections in Atlantic salmon, Salmo salar L., cultured in southern Chile and also in seals. In this study, the host-pathogen interaction between S. phocae and seven types of cell lines (fish and mammalian) was examined using an indirect fluorescent antibody and confocal microscopy (CM). Chinook salmon embryo (CHSE-214), epithelioma papulosum cyprini (EPC), salmon head kidney (SHK-1) and Atlantic salmon kidney were used as the fish cell lines, while human cervix epithelial adenocarcinoma (HeLa), African green monkey kidney fibroblast (Cos-7) and mouse leukaemic monocyte macrophage (Raw 264.7) were included as mammalian cell lines. Streptococcus phocae type strain ATCC 51973 T and isolates LM-08-Sp and P23 were selected as representatives from the salmon and seal host, respectively. For the CM examination, monolayers seeded on round coverslips were studied at 2- and 20-h post-inoculation (pi). The results showed that there is no common infectivity pattern between the three S. phocae strains at 2-h pi and the cell lines tested, regardless of the source of isolation (seal or salmon). All S. phocae strains could internalize and were found inside the fish and mammalian cell cytoplasm after 20-h pi. Regardless of the cells studied (fish or mammal) and incubation (2 and 20h), S. phocae was never observed inside the nuclei. Seal and salmon isolates showed the highest number of bacteria entering into the primate cell lines (HeLa and Cos-7) from 2-h pi, while ATCC 51973 T was not found outside or inside the HeLa and Cos-7 cells. © 2012 Blackwell Publishing Ltd.